Progress and challenges in achieving sustainable development goals in India: A comprehensive review - Tripathi, Santosh Kumar; Farooque, Asma; Ahmad, Syed Afzal (Edelweiss Applied Science and Technology, 2025)
The SDGs, or the Sustainable Development Goals, adopted via the United Nations (UN) in 2015, provide a global blueprint for tackling key social, environmental, and economic challenges. As a country with a diverse and significant population, India's progress towards these goals presents unique opportunities and challenges. This review article critically analyses India's progress in attaining the Sustainable Development Goals (SDGs), investigates the challenges faced, and proposes potential ways to accelerate advancements towards sustainable development. The article utilizes a wide array of secondary data to thoroughly evaluate the present condition of SDG implementation in India. The analysis focuses on government policies, creative interventions, and successful case studies. It provides recommendations for future action, contributing to a more detailed knowledge of India's efforts and the wider global discussion on sustainable development.